Synthesis, Characterization and Acute Anti-inflammatory Evaluation of New Mefenamic Acid Derivatives Having 4-Thiazolidinone Nucleus - Mustafa Hussein al; Muthanna S. Farhan (College of Pharmacy University of Baghdad, 2019)
Mefenamic acid (MA) widely used probably due to having both anti-inflammatory and analgesic activity, the main side effects of mefenamic acid include gastrointestinal tract (GIT) disturbance mainly diarrhea, peptic ulceration, and gastric bleeding. The study aimed to synthesize derivatives of mefenamic acid with more potency and to decrease the drug's potential side effects, new series of 4-thiazolidinone derivatives of mefenamic acid were synthesized IVa-g. The synthetic procedures for target compounds and their intermediates are designed to be as follows: acylation of secondary amine of mefenamic acid by chloroacetylchloride to produce compound (I), then reaction between compound (I) and hydrazine hydrate to produce compound (II). After that, Schiff base formation by addition of seven benzaldehyde derivatives and finally, cyclization in presence of thioglycolic acid to form 4-thiazolidinone heterocyclic ring. The characterization of the titled compounds has been established on the basis of their spectral FTIR, 1HNMR data, and by measurements of their physical properties. In vivo acute anti-inflammatory effect of the synthesized compounds was evaluated in rats using egg-white (i.p) induced edema model of inflammation. The tested compounds and the reference drug produced significant reduction of paw edema with respect to the effect of dimethyl sulfoxide 10%v/v (control group). Compound IVe showed more potent effect than mefenamic acid at 240-300 min, while at time 300 min, compounds IVa and IVd exhibit more potent anti-inflammatory effect than mefenamic acid (50mg/kg, i.p.). On the other hand compound IVc exhibited lower anti-inflammatory effect.